Cytogenetic studies in primary amenorrhoea cases - Elham Ghadirkhomi; Akram Ghdirkhomi; Seyed Abdolhamid Angaji (Wolters Kluwer Medknow Publications, 2022)
Background: Amenorrhoea is considered a kind of menstrual disorder in a woman of reproductive age. It is a symptom with many potential causes such as an abnormality in the hypothalamic-pituitary-ovarian axis, anatomical abnormalities of the genital tract or functional causes. Aims: In this study, we aimed to investigate chromosomal abnormalities in patients presenting with primary amenorrhoea. Setting and Design: This study was conducted in the medical genetic laboratory. Materials and Methods: Chromosomal analysis was carried out in 134 cases that were referred to the human genetic laboratory from 2010 to 2017, employing (GTG) Giemsa banding. Statistical Analysis Used: Statistical analyses were carried out by Microsoft Office Excel (2019). Results: The karyotype results revealed 77.6% (n = 104) with normal chromosome composition while 22.38% (n = 30) showed chromosomal abnormalities. Among the patients with abnormal chromosome constituents, 53.54% exhibited numerical aberration and 46.66% showed structural abnormalities. Conclusion: The present study has emphasised that karyotyping is one of the fundamental investigations in the evaluation of primary amenorrhoea.